Outer-Membrane-Vesicle–Associated O Antigen, a Crucial Component for Protecting Against Bordetella parapertussis Infection - Bottero, Daniela; Zurita, María Eugenia; Gaillard, María Emilia; Carriquiriborde, Francisco; Martin Aispuro, Pablo; Elizagaray, Maia; Bartel, Erika; Castuma, Celina; Hozbor, Daniela (Frontiers in Immunology, 2018)
Bordetella parapertussis is a respiratory-disease pathogen producing symptomatology similar to that of pertussis but of underestimated incidence and with no specific vaccine existing. We recently designed a vaccine candidate from B. parapertussis outer-membrane vesicles (OMVs) that proved to be safe and protective in a murine-infection model. Based on protection recently reported for the B. parapertussis O antigen in aqueous solution, we assessed here whether the B. parapertussis O-antigen-containing lipopolysaccharide (BppLPS-O+) embedded in the membranes, as present in B. parapertussis-derived OMVs (OMVs(Bpp-LPS-O+)), was the component responsible for that previously observed protection by OMVs. By performing a comparative study with OMVs from a human strain with undetectable O antigen (OMVs(Bpp-LPS-O-)), we demonstrated that the OMVs(Bpp-LPS-O+), but not the OMVs(Bpp-LPS-O-), protected mice against sublethal B. parapertussis infections. Indeed, the B. parapertussis loads were significantly reduced in the lungs of OMVs(Bpp-LPS-O+) -vaccinated animals, with the CFUs recovered being decreased by 4 log units below those detected in the nonimmunized animals or in the animals treated with the OMVs(Bpp-LPS-O-), (p<0.001). We detected that the OMVs(Bpp-LPS-O+) induced IgG antibodies against B. parapertussis whole-cell lysates, which immunocomponents recognized, among others, the O antigen and accordingly conferred protection against B. parapertussis infection, as observed in in-vivo–passive-transfer experiments. Of interest was that the OMVs(Bpp-LPS-O+) -generated sera had opsonophagocytic and bactericidal capabilities that were not detected with the OMVs(Bpp-LPS-O-)-induced sera, suggesting that those activities were involved in the clearance of B. parapertussis. Though stimulation of cultured spleen cells from immunized mice with formulations containing the O antigen resulted in gamma interferon (IFN-γ) and interleukin-17 production, spleen cells from OMVs(Bpp-LPS-O+) -immunized mice did not significantly contribute to the observed protection against B. parapertussis infection. The protective capability of the B. parapertussis O antigen was also detected in formulations containing both the OMVs derived from B. pertussis and purified BppLPS-O+. This combined formulation protected mice against B. pertussis along with B. parapertussis.